Research and intuition - Zhao, Liangyi. (2011)
One cannot help but feel good for being a mathematician after reading the above quote. After all,if a man such as Lord Kelvin, a well-known English man who was primarily a physicist, spoke well of mathematicians and more in particular a French mathematician, then we indeed all have great cause to rejoice at our own profession. Deriving(1) takes nothing more than a little knowledge in multi-variable calculus and some adhoc proofs require evenless, although at ruly rigorous proof needs some convergence arguments in the execution. But the ideas behind(1) are not deep.